Sustainable Modernity The Nordic Model and Beyond - Witoszek, Nina; Midttun, Atle (Routledge Studies in Sustainability, 2018)
The Open Access version of this book, available at https://www.taylorfrancis.com/books/e/9781351765633, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. In the 21st century, Norway, Denmark and Sweden remain the icons of fair societies, with high economic productivity and quality of life. But they are also an enigma in a cultural-evolutionary sense: though by no means following the same socio-economic formula, they are all cases of a "non-hubristic", socially sustainable modernity that puzzles outside observers. Using Nordic welfare states as its laboratory, Sustainable Modernity combines evolutionary and socio-cultural perspectives to illuminate the mainsprings of what the authors call the "well-being society". The main contention is that the Nordic uniqueness is not merely the outcome of one particular set of historical institutional or political arrangements, or sheer historical luck; rather, the high welfare creation inherent in the Nordic model has been predicated on a long and durable tradition of social cooperation, which has interacted with global competitive forces. Hence the socially sustainable Nordic modernity should be approached as an integrated and tightly orchestrated ecosystem based on a complex interplay of cooperative and competitive strategies within and across several domains: normative-cultural, socio-political and redistributive. The key question is: Can the Nordic countries uphold the balance of competition and cooperation and reproduce their resilience in the age of globalization, cultural collisions, the digital economy, the fragmentation of the work/life division, and often intrusive EU regulation? With contributors providing insights from the humanities, the social sciences and evolutionary science, this book will be of great interest to students and scholars of political science, sociology, history, institutiona